2012
DOI: 10.1155/2012/848042
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HLA-A24-Restricted Novel T Cell Epitope Peptides Derived from P-Cadherin and Kinesin Family Member 20A

Abstract: We here identified human leukocyte antigen-(HLA-)A∗2402-restricted epitope peptides from Cadherin 3, type 1, P-cadherin (CDH3) and kinesin family member 20A (KIF20A) that were found to be specifically expressed in cancer cells through genome-wide expression profile analysis. CDH3-10-807 peptide and KIF20A-10-66 peptide successfully induced specific CTL clones, and these selectively responded to COS7 cells expressing both HLA-A∗2402 and respective protein while did not respond to parental cells or COS7 cells ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Knockdown of KIF20A in pancreatic cancer cells can significantly inhibit cell proliferation,17,18 indicating the significance of its overexpression in human cancers. Studies have also reported that several peptides derived from KIF20A can be helpful to activate the immune system and kill the cancer cells which endogenously express KIF20A antigen 16,19,20. Several groups are carrying out the phase I/II clinical trials for immunotherapy using these KIF20-derived peptides 21.…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of KIF20A in pancreatic cancer cells can significantly inhibit cell proliferation,17,18 indicating the significance of its overexpression in human cancers. Studies have also reported that several peptides derived from KIF20A can be helpful to activate the immune system and kill the cancer cells which endogenously express KIF20A antigen 16,19,20. Several groups are carrying out the phase I/II clinical trials for immunotherapy using these KIF20-derived peptides 21.…”
Section: Introductionmentioning
confidence: 99%
“…KIF20A has been reported to be a promising immunotherapeutic target for cancers. Studies have reported that 2 short peptides (SP) derived from KIF20A, KIF20A-A2 , and KIF20A-A24 66-75 stimulated CTLs, which kill cancer cells endogenously expressing KIF20A antigen and that KIF20A-specific CTLs were present in peripheral blood mononuclear cells (PBMC) obtained from patients with pancreatic cancer (1,4). Phase I/II clinical trials of cancer immunotherapy for lung cancer, pancreatic cancer, and cholangiocellular carcinoma using KIF20A-derived SP are underway.…”
Section: Introductionmentioning
confidence: 99%
“…The targeting oncogenic antigens can avoid the immune escape of cancer cells by lacking these proteins [22,23] . Epitope peptides of several oncoantigens such as kinesin family member 20A (KIF20A), lymphocyte antigen 6 complex locus K (LY6K), DEP domain-containing 1 (DEPDC1), forkhead box M1 (FOXM1), cell division cycleassociated 1 (CDCA1), cadherin 3/P-cadherin (CDH3), insulin-like growth factor-II mRNAbinding protein 3 (IMP-3) and others have been developed for clinical trials [24][25][26][27][28][29][30][31][32][33] .…”
Section: Oncoantigensmentioning
confidence: 99%